2020
DOI: 10.1021/acssynbio.9b00527
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Analysis of a Rationally Designed Aldehyde Dehydrogenase Gives Insights into Improved Activity for the Non-Native Cofactor NAD+

Abstract: The aldehyde dehydrogenase from Thermoplasma acidophilum was previously implemented as a key enzyme in a synthetic cellfree reaction cascade for the production of alcohols. In order to engineer the enzyme's cofactor specificity from NADP + to NAD + , we identified selectivity-determining residues with the CSR-SALAD tool and investigated further positions based on the crystal structure. Stepwise combination of the initially discovered six point mutations allowed us to monitor the cross effects of each mutation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…The current results confirm that Asp37-containing NcmD prefers NAD + (Kallberg et al, 2002), which has been confirmed by resultant in vitro enzymatic assays. Generally, the catalytic activities decrease significantly when the SDRs are not compatible with cofactors, which have been observed from NcmD enzymatic assays, and similar results are also revealed from other SDRs (Moon et al, 2012;Takase et al, 2014;Cao et al, 2019;Gmelch et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…The current results confirm that Asp37-containing NcmD prefers NAD + (Kallberg et al, 2002), which has been confirmed by resultant in vitro enzymatic assays. Generally, the catalytic activities decrease significantly when the SDRs are not compatible with cofactors, which have been observed from NcmD enzymatic assays, and similar results are also revealed from other SDRs (Moon et al, 2012;Takase et al, 2014;Cao et al, 2019;Gmelch et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…Transketolase (TktA) kinetics (Figure S2) were measured in a coupled approach with glyceraldehyde specific aldehyde dehydrogenase taAldH (M42) [50] by measuring reduction of NAD + . To test whether M42 activity is reduced by formaldehyde, activity of M42 was tested on glyceraldehyde by measuring the reduction of NAD + in presence of 0 to 20 mM formaldehyde (Figure S3).…”
Section: Methodsmentioning
confidence: 99%
“…Gluconobacter oxydans 621H SDR low promiscuity WP_172493137 [143] PyAeADHII Pyrobaculum aerophilum MDR low promiscuity 4JBH [30] PasCR Pichia pastoris GS115 SDR promiscuous XP_002491455 [144] TaAIDH Thermoplasma acidophilum ALDH_SF multiple substrates CAC11938 [145][146][147] AtADH Arabidopsis thaliana MDR multiple substrates P06525 [148] BgADH3 Burkholderia gladioli CCTCC M2012379 SDR low promiscuity WP_172493137 [149] AcCR Acetobacter sp. CCTCC M209061 SDR multiple substrates MF419650 [150] ChKRED20 Chryseobacterium sp.…”
Section: Hvadh2mentioning
confidence: 99%